Trajectoires et subjectivités italo-québécoises : le processus identitaire de la deuxième génération tel que conçu par Marco Micone, Mary Melfi et Paul Tana - Hélie-Martel, Anaïs (Université de Montréal, 2017)
This thesis focuses on the process of identity formation of second generation Italo-Quebeckers during the second wave of migration. More precisely, it looks at the creative works of Marco Micone, Mary Melfi and Paul Tana in order to reveal certain aspects of identity that are contained in works of fiction. It is through their vision that it is possible to identify several narrative frames that underscore different migratory and settlement trajectories in Quebec. These visions also expose the challenge of the (re)definition of self in a modern and bilingual society. Instead of defining a “global” identity, this thesis is more interested in the elements that shape, affect, and above all, put pressure on the (re)identification of this generation. Drawing upon the sources employed in this thesis, three main themes emerge as modelling elements of identity for the second generation of Italo-Québécois: the relationship to language(s), gender relations, and intergenerational dynamics. All these themes are explored by each of the creators, although in different ways. This reinforces the idea that it is impossible to talk about a common Italian-Québécois identity and that it is preferable to talk about Italian-Quebecois subjectivities. Ultimately, it is a matter of disclosing how literary and creative works encourage us to rethink the establishment of Italians in Quebec, as well as their vision of Quebec society.
Keywords: History - Canadian / Histoire - Canadienne (UMI : 0334); Italians from Quebec; Marco Micone; Mary Melfi; Montréal; Paul Tana; Québec; gender; identity; identité; immigration italienne; intergenerational; intergénérationnel; italian immigration; italo-québécois; langage; language; langue; rapport de genre; subjectivity; subjectivité